Automated Wavelength Alignment in a 4 × 4 Silicon Thermo-Optic Switch Based on Dual-Ring Resonators - Qingming Zhu; Xinhong Jiang; Yanping Yu; Ruiyuan Cao; Hongxia Zhang; Danping Li; Yanbo Li; Li Zeng; Xuhan Guo; Yong Zhang; Ciyuan Qiu (IEEE Photonics Journal)
We propose and experimentally demonstrate an automated resonance wavelength alignment scheme for an O -band 4 × 4 thermo-optic optical switch using dual-ring resonators. In this scheme, a new control algorithm based on saddle point searching is employed to align dual-input switching elements (SEs) and therefore the 4 × 4 switch. The proposed scheme is proven effective by demonstrating eight routing configurations for two 10-Gb/s data channels. The insertion losses of the three-stage SEs are ≤6.9 dB, and the crosstalk values are below −13.6 dB. Besides, the tolerance of the switch to the wavelength misalignment between the two optical input signals is measured. Negligible performance degradations are observed when the two channels are spaced by 0.05 nm.